INFLUENCE OF SOIL FERTILITY ON THE ABILITY OF SCOTS PINE (Pinus sylvestris L.) TO ADAPT TO TECHNOGENIC POLLUTION - Zavyalov, Konstantin; Ivanova, Natalya; Potapenko, Anton; Ayan, Sezgin (FapUNIFESP (SciELO), 2019)
ABSTRACT The purpose of the research is to identify the effect of soil factor on the ability of Scots pine to adapt to technogenic pollution based on comparative analysis of radial increment of the species which grows on soils of different fertility. The null hypothesis that soil fertility is a significant factor for adaptation was tested. The research area i.e. the plantation created in 1983 and exposed to pollution of aero-technogenic emissions of magnesium production Satka/Chelyabinsk Region/Russia, is located within the central part of the subzone of coniferous-broad-leaved and South-taiga coniferous forests of the Southern Urals. The analysis of annual growth rings (AGR) of Scots pine growing on soils of different fertility allowed us to estimate the effect of soil factor on the ability of Scots pine to adapt to magnesite pollution. As results of the research it was found that the differences in the AGR of Scots pine growing on soils of different fertility was statistically significant under the same level of technogenic pollution. During the investigation period (1994-2010), the AGR of Scots pine on fertile soils were significantly higher than those of on poor soils for 7 years. It was revealed that the positive effect of soil fertility on the Scots pine growth is leveled at the level of pollution exceeding 6-10 thousand tons per year of gaseous emissions and 25-30 thousand tons per year of total emissions. It was also found that soil fertility allows better adaptation of Scots pine to low temperatures, and more actively grow on sites with increasing precipitation.
Keywords: Dendrochronological analysis; Scots pine; Forest ecosystem; Forest planting; forest planting, dendrochronological analysis, forest ecosystem, aero-technogenic.; Aero-technogenic; 2. Zero hunger; 13. Climate action; 15. Life on land